APPLICATION OF DATA MINING IN PREDICTING THE AMOUNT OF RESTAURANT TAX REVENUE USING C4.5 - Afriza, Roby; Nurmayanti, Nurmayanti; Parida, Merri; Rahmatullah, Sidik (Jurnal TAM (Technology Acceptance Model), 2023)
Regional taxes are one of the important sources of regional income to finance the implementation of regional government in the context of serving the community and realizing regional independence. Restaurant tax is one of the regional taxes collected by the Way Kanan Regency Regional Revenue Agency and one of the determinants of the increase in Way Kanan District Original Revenue (PAD). Adapum This research raises the problem of not achieving the Restaurant Tax target in 2023. In this study using Data Mining there are various methods in data mining including the C4.5 algorithm. The C4.5 approach can forecast an increase in restaurant taxes, and the computation of the C4.5 algorithm yields the following results. From the results of calculating the 2018-2022 data above using Microsoft Excel, it is known that Class Recommendations totaling 185 are classified as Yes and No, 0 are classified as Yes but No, Next Class No totaling 65 is classified as No, and 0 Yes is classified as No, with a total data of 250. Microsoft Excel and Google Colab programs have been used to implement the C4.5 algorithm. Implementation of the C4.5 Algorithm has been carried out using Microsoft Excel and Googlel Colab applications. The result is that the description of all formulas and predictive results is simpler than the results of manual calculations through Microsoft excel using the C4.5 Algorithm which has an accuracy of 75%, and then proven by Google Colab with results of 100% accuracy.